Prompt and nonprompt ψ(2S) production in pPb collisions at √sNN = 8.16 TeV - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Langenbruch, Christoph; et al. (Journal of high energy physics, 2024)
The production of ψ(2S) mesons in proton-lead collisions at a centre-of-mass energy per nucleon pair of = 8.16 TeV is studied with the LHCb detector using data corresponding to an integrated luminosity of 34 nb−1. The prompt and nonprompt ψ(2S) production cross-sections and the ratio of the ψ(2S) to J/ψ cross-section are measured as a function of the meson transverse momentum and rapidity in the nucleon-nucleon centre-of-mass frame, together with forward-to-backward ratios and nuclear modification factors. The production of prompt ψ(2S) is observed to be more suppressed compared to pp collisions than the prompt J/ψ production, while the nonprompt productions have similar suppression factors.